2021
DOI: 10.1002/adhm.202100453
|View full text |Cite
|
Sign up to set email alerts
|

Delivery by Dendritic Mesoporous Silica Nanoparticles Enhances the Antimicrobial Activity of a Napsin‐Derived Peptide Against Intracellular Mycobacterium tuberculosis

Abstract: Tuberculosis remains a serious global health problem causing 1.3 million deaths annually. The causative pathogen Mycobacterium tuberculosis (Mtb) has developed several mechanisms to evade the immune system and resistances to many conventional antibiotics, so that alternative treatment strategies are urgently needed. By isolation from bronchoalveolar lavage and peptide optimization, a new antimicrobial peptide named NapFab is discovered. While showing robust activity against extracellular Mtb, the activity of N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 62 publications
1
18
0
Order By: Relevance
“…We exposed embryos for 24 h, starting at 24 h post fertilization (hpf), when most organ systems have already developed and are functional. Transparency of the embryos allows for the evaluation, not only of mortality, but also of sublethal cytotoxicity (necrosis, lysis), developmental toxicity (developmental delay, malformations), or toxicity affecting specific organ systems, in particular cardiotoxicity (heart edema, reduced circulation) and neurotoxicity (reduced touch escape response), as mentioned in prior studies [20,21]. Gran1 neither effected embryo viability nor caused sublethal toxicity (Figure 4E).…”
Section: Off-target Effects and Toxicity Of Gran1mentioning
confidence: 73%
See 1 more Smart Citation
“…We exposed embryos for 24 h, starting at 24 h post fertilization (hpf), when most organ systems have already developed and are functional. Transparency of the embryos allows for the evaluation, not only of mortality, but also of sublethal cytotoxicity (necrosis, lysis), developmental toxicity (developmental delay, malformations), or toxicity affecting specific organ systems, in particular cardiotoxicity (heart edema, reduced circulation) and neurotoxicity (reduced touch escape response), as mentioned in prior studies [20,21]. Gran1 neither effected embryo viability nor caused sublethal toxicity (Figure 4E).…”
Section: Off-target Effects and Toxicity Of Gran1mentioning
confidence: 73%
“…Embryos were categorized within each of these toxicity categories into several classes of severity. Chi-square test was used to calculate whether the distribution of embryos into toxicity classes [21] differed significantly between the negative control and the test substances.…”
Section: Toxicity Of Gran1 Against Macrophages and Zebrafishmentioning
confidence: 99%
“…11C). 253 Similarly, MSNs loaded with NZX 256 and NapFab 257 AMPs also showed potent antituberculosis properties in vitro (against Mycobacterium bovis , M. bovis (BCG)) and in vivo (against M. tuberculosis H37Rv). Sharma et al designed Pep-H AMP, identified from human neutrophil peptide-1, and conjugated on chitosan and Au NPs.…”
Section: Fighting Infectionsmentioning
confidence: 98%
“…E. coli and Enterococcus faecalis ( E. faecalis ) are most prevalent bacteria in UTIs. 257 Generally, the antimicrobial activity of conjugated AMPs is compromised due to protein adsorption or biofilm formation on the top of the AMP-coated surfaces. This challenge can be overcome by modifying the physicochemical properties of catheters such as wettability and surface charge.…”
Section: Fighting Infectionsmentioning
confidence: 99%
“…Active targeting provides nanosystems of specificity to the site of infection, being relevant in the case of intracellular infections, where bacteria overcome the host immune system by surviving in human cells. In this sense, MSNs have already been used as nanocarriers of anti-tuberculosis drugs [81,82], silver [83] or antimicrobial peptides [84] as antimycobacterial agents against intracellular Mycobacterium tuberculosis, the pathogen responsible for tuberculosis. This section describes recent advances in the pursuit of MSNs at the two main targets concerning infection management, the bacterium and the biofilm.…”
Section: Msns For Targeted Delivery Of Antimicrobialsmentioning
confidence: 99%